Coriolis coupling effects in quantum dynamics calculations of the reactions H + NT (a1?) and isotopic effect - Hekim, Seda (Springer Heidelberg, 2021)
The time-dependent wave packet method was used to investigate the dynamics of the H + NT (a(1)Delta) reaction and its isotopic variants based on the modified NH2 ((A) over tilde (2) A(1)) potential energy surface. The reaction probabilities, cross section, and rate constants were obtained for depletion and exchange channel of H + NT reaction using the Coriolis coupling (CC) method. The comparison of CC and centrifugal sudden (CS) results shows that the CC effect plays a significant role in the title reaction. The isotopic effect has been pointed out by comparing it with previous NH + H and ND + H results.
Keywords: Potential-Energy Surface; Real Wave-Packets; N(D-2)+H-2 Reaction; Cross-Sections; Flux Analysis; Ground-State; H-2; Probabilities; Scattering; Atoms